2019
DOI: 10.1016/j.clinbiochem.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating NT-proBNP but not soluble corin levels were associated with preeclampsia in pregnancy-associated hypertension

Abstract: Background: Corin is a serine protease known to convert B-type natriuretic peptide (BNP) prohormone into BNP and its amino-terminal fragment (NT-proBNP). In mice lacking corin, high blood pressure and proteinuria were found at late gestational stages, with associated delayed trophoblast invasion and impaired spiral artery remodeling in the uterus. We hypothesize that both NT-proBNP and soluble corin elevation predict the presence of preeclampsia in pregnant patients with hypertension. Methods:We prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Other studies have identified that particularly women with EPE have altered cardiac structure and function, along with increased circulating levels of the well-established cardiovascular biomarker NTproBNP. 56,74,75 The dysregulated CVD biomarkers identified in the preeclamptic pregnancies likely reflect heterogeneous physiological and pathological processes linked to the pregnancy stress of PE, and particularly to EPE, which is also linked to the highest degree of placental cellular stress (e.g endoplasmic reticulum stress). 76 Whether these biomarkers also can be used for targeting women at highest risk for long-term CVD, and therefore for intervention trials and personalized medicine, is an exciting possibility to explore in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified that particularly women with EPE have altered cardiac structure and function, along with increased circulating levels of the well-established cardiovascular biomarker NTproBNP. 56,74,75 The dysregulated CVD biomarkers identified in the preeclamptic pregnancies likely reflect heterogeneous physiological and pathological processes linked to the pregnancy stress of PE, and particularly to EPE, which is also linked to the highest degree of placental cellular stress (e.g endoplasmic reticulum stress). 76 Whether these biomarkers also can be used for targeting women at highest risk for long-term CVD, and therefore for intervention trials and personalized medicine, is an exciting possibility to explore in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…During normal pregnancy, BNP is maintained at a relatively low level (a median level of <20 pg/mL) (12,19). However, the PE women were shown to have significantly higher BNP levels in the third trimester (10)(11)(12)(13)(14). The BNP level of PE with severe features was higher than that of PE without severe features (10,12), while the BNP of early-onset PE was higher than lateonset PE (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on BNP in PE have mainly focused on its diagnosis or prediction of the disease and its relationship with the associated cardiovascular complications. In PE, the BNP levels reflect the severity of the PE (10)(11)(12)(13)(14), and elevated BNP levels are associated with ventricular systolic or diastolic dysfunction (24)(25)(26). Kumari et al (13) found that BNP levels in women with chronic hypertension and gestational hypertension who later superimposed or progressed to PE were significantly higher than those who did not develop PE, and the ROC curve analysis showed that BNP had a good value in predicting the development of PE in the study population (AUC =0.7406, 95% CI: 0.6543-0.827, P<0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an association of NT-proBNP levels with RAS component levels in pregnant women [219]. Some studies have focused on the increased circulating levels of natriuretic peptides in pregnant women suffering from PE, mainly in its early and severe form [219][220][221]. PE involves a failure of the maternal cardiovascular system to adapt to the demands of pregnancy, therefore a cardiac origin of NT-proNBP was first attributed.…”
Section: Nt-probnp In Pregnancy and In Covid-19 Pregnanciesmentioning
confidence: 99%